(untitled) (Eurasian Journal of Philology Science and Education, 2025)
Despite the fact that the phenomenon of national identity in Kazakhstan science has been studied quite extensively and deeply from different social and humanitarian angles, to date, no specific approach has been developed from the standpoint of foreign language teaching that allow the development of the topic under study. Domestic researchers agree that teaching foreign languages, along with general advantages, also has disadvantages that negatively affect national identity, among other things, if measures are not taken adequate to external threats during the educational process. The aim of the resarch is to study of textbooks intended for teaching foreign language as well as determine the ideas of students about national identity. The method of the study is mix method which was designed as a descriptive study and qulititive research literature revew. To determine the ideas of the university students about national identity in English classes used descriptive study in the model of survey. The questionnaire presented to the attention of the students pursued the goal of:to determine the attitude of students to the problem of national identity; to determine the experience and practice of using materials with national flavor in the study of the English language and to find out the possible loyalty of students to a foreign language and culture, or whether they have any feelings of internal discomfort regarding the spread of the English language and culture. The data of the study are collected via the a survey of 15 students was conducted and analysing English language textbooks for Kazakhstani students. The main results of the study consider ways to adapt foreign textbooks for developing students the national identity. Keywords: national identity, foreign language and culture, study of textbooks.